Rigid spine syndrome with respiratory failure. Issue 9 (September 1990) - Morita, H; Kondo, K; Hoshino, K; Maruyama, K; Yanagisawa, N
Abstract : The pathogenesis and therapy of respiratory failure in the rigid spine syndrome are discussed in two cases who improved with respiratory assistance. In both cases, the partial pressures of oxygen and carbon dioxide were reversed in arterial blood gas analysis and %VC was less than 30%. Remission from respiratory failure has been obtained by the use of a ventilator during the night. The cause of the respiratory failure in both cases was severe restrictive respiratory dysfunction due to extreme flattening of the chest and fixation of the thorax during respiration as a result of contracture of costovertebral joints. All the previously reported cases of the rigid spine syndrome with respiratory failure died. Appropriate use of the ventilator can improve the prognosis.